2015
DOI: 10.1039/c5dt00742a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural studies, kinetic stability, and oxidation catalysis of the late first row transition metal complexes of 4,10-dimethyl-1,4,7,10-tetraazabicyclo[6.5.2]pentadecane

Abstract: Synthetic details for 4,11-dimethyl-1,4,8,11-tetraazabicyclo[6.5.2]pentadecane, the dimethyl ethylene cross-bridged homocyclen ligand are presented for the first time. Its novel Mn(2+), Fe(2+), Mn(3+), and Fe(3+) complexes have been synthesized and characterized. X-ray crystal structures were obtained for both manganese complexes, along with five additional Co(3+), Cu(2+), and Zn(2+) structures, the first structural characterization of complexes of this ligand. Each complex has the cis-V configuration of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Cross‐bridged tetraazamacrocycles offer an advantage for this purpose in that they very slowly decomplex from the Cu 2+ ion in aqueous solution due to the rigidity and topological complexity provided by the short cross‐bridge . The likely major mechanism of inactivation of Cu 2+ complexes in vivo is through loss of ligand resulting in free, inactive Cu 2+ ,. However, an additional proposed indicator of in vivo stability is resistance toward reduction to Cu + followed by loss of the more labile Cu + ion .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross‐bridged tetraazamacrocycles offer an advantage for this purpose in that they very slowly decomplex from the Cu 2+ ion in aqueous solution due to the rigidity and topological complexity provided by the short cross‐bridge . The likely major mechanism of inactivation of Cu 2+ complexes in vivo is through loss of ligand resulting in free, inactive Cu 2+ ,. However, an additional proposed indicator of in vivo stability is resistance toward reduction to Cu + followed by loss of the more labile Cu + ion .…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, reversibility of the Cu 2+ /Cu + reduction wave has been used as an indicator of potential in vivo stability, along with kinetic inertness towards aqueous hydrolysis. In combination with the kinetic stability of the cyclam‐based ligand 1 , the reversibility of the reduction of these cyclam‐based ligands bodes well for their in vivo stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of decahydro-2a,4a,6a,8a-tetraazacyclopenta[fg]acenaphthylene was carried out via literature methods. [11]…”
Section: Methodsmentioning
confidence: 99%
“…[8] [9] Recently we have been interested in the use of this complex type as oxidation catalysts. [10] [11] [12] A recent papers by Que, et al, has shown that addition of a pyridyl pendant arm to a tetraazamacrocycle can result in new and improved oxidation catalysis. [13] The literature contains numerous other pyridyl pendant armed tetraazamacrocycles, indicating a general interest in the community and known synthetic techniques for adding pendant pyridyl donors.…”
Section: Introductionmentioning
confidence: 99%